PEDAGOGICAL AND PSYCHOLOGICAL BASIS OF COOPERATION BETWEEN PARENTS AND EDUCATIONAL INSTITUTION - Shodmonova, Dinora (Журнал Педагогики и психологии в современном образовании, 2024)
A common symptom of dysfunction of the modern Russian family is the disharmony of family relationships, which is formed due to the lack of knowledge among young people about the patterns of functioning of the family system, because of the insufficient level of positive communication skills development and the ability to resolve family conflicts, sometimes due to psychological incompatibility of young spouses (Kochergina & Kirjushina, 2018).